Program Kelas Keluarga - Zulliati Zulliati; Ali Rakhman Hakim; Nita Hestiyana (Jurnal Sains dan Kesehatan, 2022)
The current condition of maternal and child health in Indonesia is still very important to improve and receive special attention. According to 2018 RISKESDES data, it is estimated that around 1 mother dies every hour due to pregnancy, childbirth and postpartum and every day 401 babies die. Overall, the causes of maternal and child death are complex, involving medical aspects that must be handled by health workers. The causes of maternal death are sequentially caused by bleeding, eclampsia, infection, prolonged labor and miscarriage. Most infant deaths are caused by low birth weight (LBW) babies, difficulty breathing at birth and infections. More than half (56%) of infant deaths occur during the newborn period (0-28 days). The family class program is a program designed to implement family involvement in the process of monitoring and improving the health and welfare of mothers and children. People who are in a supportive social environment generally have better conditions compared to people without these benefits. Family support is thought to reduce the effects on an individual's mental health. (Phillips & Pittman, 2014). The Family Class Program will be in line with regional government programs in this case the Banjarmasin Mayor Program, namely the Family Assistance Program by Health workers and also family planning cadres together with PKK cadres, where this program will synergize in the family assistance process starting from prospective brides and grooms to toddlers and monitoring and evaluation will be carried out every year. The Family Class Program which is designed to directly involve cadres, families and Health workers as well as local regional officials so that these two programs can run in tandem and in a directed manner, in its implementation activities will use several innovations such as flip sheets and pocket books which will make it easier for officers to provide assistance.